A Bibliometric Analysis of Research on Bacterial Persisters. (6th January 2023) - Ju, Yuan; Zhang, Fang; Yu, Pingjing; Zhang, Yu; Zhao, Ping; Xu, Ping; Sun, Luwei; Bao, Yongqing; Long, Haiyue
Abstract : Background . In the past two decades, the surge of research on bacterial persisters has been inspired as increasingly concerning about the frequent failure of antibiotics treatment. This study was aimed at presenting a bibliometric and visualized analysis of relative publications on bacterial persisters, which offered insights into the development and research trends of this field. Methods . The Web of Science Core Collection and Ovid MEDLINE databases were utilized to retrieve relevant publications on bacterial persisters from 2001 to 2021. After manual selection, data including titles, authors, journals, author keywords, addresses, the number of citations, and publication years were subsequently extracted. The data analysis and visual mapping were conducted with Excel, SPSS, R studio, and VOSviewer. Results . In this study, 1, 903 relevant publications on bacterial persisters were included. During 2001-2021, there was an exponential growth in the quantity of publications. It was found that these studies were conducted by 7, 182 authors from 74 different countries. The USA led the scientific production with the highest total number of publications (859) and citation frequency (52, 022). The Antimicrobial Agents and Chemotherapy was the most influential journal with 113 relevant publications. The cooccurrence analysis revealed that studies on bacterial persisters focused on four aspects: "the role of persisters in biofilms, " "clinical persistent infection, " "anti-persister treatment, " and "mechanism of persister formation." Conclusion . In the past two decades, the global field of bacterial persisters has significantly increased. The USA was the leading country in this field. Mechanistic studies continued to be the future hotspots, which may be helpful to adopt new strategies against persisters and solve the problem of chronic infection in the clinic.